Dimensi Kualitas Pelayanan Islami dan Hubungannya Terhadap Kepuasan Pasien di Rumah Sakit - Hanun, Hafida Zahara; Jati, Sutopo Patria; Arso, Septo Pawelas (Ranah Research : Journal of Multidisciplinary Research and Development, 2025)
In an effort to provide optimal service, hospitals must consider quality standards involving medical and non-medical aspects. Indonesia, the world's largest Muslim-majority country, faces demand to integrate Islamic values into health care. Although the number of Islamic hospitals continues to grow, there are still challenges in understanding and implementing the quality of Islamic services consistently. This study aims to determine the dimensions of Islamic service quality and its relationship with patient satisfaction in hospitals. This study used the scoping review method with reference to PRISMA guidelines. Article searches were conducted on Google Scholar with the keywords "Islamic Hospital" OR "Sharia Hospital" AND "Quality" OR "Patient Satisfaction". The articles included in the search were then filtered by title and abstract, with inclusion and exclusion criteria limited to the last 10-year period (2014-2023), resulting in 10 articles. Key findings included aspects such as factors affecting patient satisfaction, influence of image and service quality, implementation of sharia quality indicators, and effectiveness of Islamic-based care training. These findings provide valuable insights into the dimensions of Islamic service quality and their impact on patient satisfaction in hospitals. This study described the dimensions of service quality in the context of Islamic hospitals, focusing on Servqual (Responsiveness, Assurance, Empathy, Tangibles, and Reliability). Other factors that affected patient satisfaction were effective communication, hospital image, and implementation of Islamic principles in health services to patients. Islamic hospitals need to prioritise service quality with ServQual, Islamic principles, Islamic-based training, spiritual readiness, sharia supervision, and Islamic-based health service SOPs to improve patient satisfaction.